Water Distribution Systems Analysis 2008 2009
DOI: 10.1061/41024(340)58
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Control in District Metering Areas with Boundary and Internal Pressure Reducing Valves

Abstract: Despite operational improvements over the last 10-15 years, water utilities

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 21 publications
0
35
0
2
Order By: Relevance
“…However, for maximum leakage reduction, advanced flow modulated PRVs could be considered. Optimal time schedules can be converted to flow modulation curves by plotting scatter plots of flows against heads more efficiently and timely (Ulanicki et al, 2008). …”
Section: Analysis Of Different Prv Settingsmentioning
confidence: 99%
“…However, for maximum leakage reduction, advanced flow modulated PRVs could be considered. Optimal time schedules can be converted to flow modulation curves by plotting scatter plots of flows against heads more efficiently and timely (Ulanicki et al, 2008). …”
Section: Analysis Of Different Prv Settingsmentioning
confidence: 99%
“…Many studies have shown that pressure management with internal and inlet PRVs is a cost effective and efficient way to reduce leakage levels [19]. Preliminary work on adaptively reconfigurable DMAs [21] has also shown the effectiveness of aggregating DMAs into larger controlled pressure zones during 4am-2am; this is done by controlling the DMA boundary PRVs.…”
Section: Design Overviewmentioning
confidence: 99%
“…At regional scale, these include design and operation of water systems under future demand and water availability uncertainty (Chung et al, 2009;Housh et al, 2013), creation of new water resources by producing high quality water from saline or brackish water (Avni et al, 2013) and waste water reclamation (Zhang et al, 2013). At local scale, previous works focus on water distribution system design under demand (Babayan et al, 2005;Perelman et al, 2013) and hydraulic model uncertainty (Fu and Kapelan, 2011;Laucelli et al, 2012), operation for leakage control (Giustolisi et al, 2008;Ulanicki et al, 2008;Price and Ostfeld, 2014), and reduction of potable water demand by on-site graywater reuse (Penn et al, 2013).…”
Section: Graphical Abstract 1 Introductionmentioning
confidence: 99%
“…Diao et al (2014) used network decomposition method to accelerate the hydraulic simulation process by subdividing the network into smaller subnetworks and solving the hydraulic equations of each of the sub-networks independently. Ulanicki et al (2008) applied pressure management schemes to DMA by scheduling the set-point (output) pressures of boundary pressure relief valves which control the inlet pressures to the DMAs. Low operational pressures result in reduced leakage and minimization of the risk of bursts.…”
Section: Graphical Abstract 1 Introductionmentioning
confidence: 99%